The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1159/000521102
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Subfield Volumes and Cognitive Function in Schizophrenia and Mood Disorders

Abstract: <b><i>Introduction:</i></b> The hippocampus is relevant to cognitive function in schizophrenia (SCZ) and mood disorder patients. Although not anatomically uniform, it is clearly divided into subfields. This study aimed to elucidate the relationship between hippocampal subfield volume and cognitive function in patients with SCZ, bipolar disorder (BP), and major depressive disorder (MDD). <b><i>Methods:</i></b> The study included 21 patients with SCZ, 22 with BP, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…To the best of our knowledge, this study is first to report correlation between reduced hippocampal structural connectivity and cognitive impairment in patients with schizophrenia. Reduced hippocampal volume in schizophrenia has been widely reported (Adriano et al, 2012; Narr et al, 2004), and its association with cognitive impairment has been shown in previous studies (Thoma et al, 2009; Yasuda et al, 2022). Reduced FA values in the fornix and cingulum were reported in one such study indicating abnormal integration of white matter between the hippocampus and cortex in patients with schizophrenia (Qiu et al, 2010).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…To the best of our knowledge, this study is first to report correlation between reduced hippocampal structural connectivity and cognitive impairment in patients with schizophrenia. Reduced hippocampal volume in schizophrenia has been widely reported (Adriano et al, 2012; Narr et al, 2004), and its association with cognitive impairment has been shown in previous studies (Thoma et al, 2009; Yasuda et al, 2022). Reduced FA values in the fornix and cingulum were reported in one such study indicating abnormal integration of white matter between the hippocampus and cortex in patients with schizophrenia (Qiu et al, 2010).…”
Section: Discussionmentioning
confidence: 77%
“…Structural and functional connectivity between the hippocampus and the cortical and subcortical areas has been demonstrated (Burwell, 2000;Kahn et al, 2008;Lavenex & Amaral, 2000;Witter et al, 2000). Hippocampal pathology is related to some of the cognitive deficits in schizophrenia (Harrison, 2004;Yasuda et al, 2022), major depression disorder (O'Brien et al, 2004) and bipolar disorder (Cao et al, 2016). Recently, it has become possible to estimate structural probabilistic connectivity between brain regions by ProbtrackX program in FMRIB Software Library (FSL; Behrens group but not in the healthy control, major depressive disorder or bipolar disorder groups.…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal substructure volume atrophy has also been confirmed in first-episode drug-naive psychotic patients; moreover, the same study found a non-linear relationship between dentate gyrus/CA4 volume changes and antipsychotic dose after 12 weeks of risperidone or aripiprazole treatment 29 . Further, more recent studies have found significant associations of cognitive composite and declarative memory scores with the volumes of multiple hippocampal substructures in schizophrenia 25,30 .…”
Section: Introductionmentioning
confidence: 97%
“…An association between HF morphologic and physiological abnormalities and cognitive deficits in individuals with schizophrenia has been consistently shown [ 14 18 ]. At the subfield level, negative correlations between CA1, CA2/3, CA4/DG, and subiculum volumes and cognitive functioning in individuals with schizophrenia have been demonstrated, whereby verbal memory seems to be particularly affected [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%